2018
DOI: 10.1002/ccr3.1424
|View full text |Cite
|
Sign up to set email alerts
|

Discordant NIPT result in a viable trisomy‐21 pregnancy due to prolonged contribution to cfDNA by a demised trisomy‐14 cotwin

Abstract: Key Clinical MessageOne of the confounders in noninvasive prenatal testing (NIPT) is the vanishing twin phenomenon. Prolonged contribution to the maternal Cell‐free DNA (cfDNA) pool by cytotrophoblasts representing a demised, aneuploid cotwin may lead to a false‐positive outcome for a normal, viable twin. We show that a vanishing trisomy‐14 twin contributes to cfDNA for more than 2 weeks after demise.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 10 publications
0
19
0
Order By: Relevance
“…The fetal demise of a cotwin has been known as an important factor in association with false-positive NIPT results. 11,[23][24][25][26] Substantial proportions of false-positive NIPT results ranging from an estimated 15% to 33% might be caused by unrecognized fetal demise. [27][28][29] Critical questions of NIPT clinical practice include how long the residual cfDNA from a deceased cotwin remains in the maternal circulation and if NIPT should be used when the fetal demise of a cotwin has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…The fetal demise of a cotwin has been known as an important factor in association with false-positive NIPT results. 11,[23][24][25][26] Substantial proportions of false-positive NIPT results ranging from an estimated 15% to 33% might be caused by unrecognized fetal demise. [27][28][29] Critical questions of NIPT clinical practice include how long the residual cfDNA from a deceased cotwin remains in the maternal circulation and if NIPT should be used when the fetal demise of a cotwin has been identified.…”
Section: Discussionmentioning
confidence: 99%
“…In three patients, the NIPT results showed evidence of aneuploidy that was not present following invasive sampling. Such results can be caused by confined placental mosaicism (CPM), undetected twin pregnancies with foetal demise or maternal aneuploidy (e.g., due to neoplasia) (26) or maternal copy-number variants. One such trisomy 18 result from our study was confirmed to be due to CPM.…”
Section: Cohortmentioning
confidence: 99%
“…Fetal demise in a multifetal pregnancy can complicate aneuploidy screening as the cell-free DNA (cfDNA) from the non-viable conception may lead to a non-invasive prenatal testing result that is discordant with that of the viable fetus 1,2 . This poses a challenge for healthcare providers in identifying an appropriate prenatal genetic screening option in such cases.…”
mentioning
confidence: 99%